Usadha Bali di Era Digital: Studi Kasus Persepsi, Praktik, dan Minat Generasi Muda terhadap Tanaman Obat Lokal di Bali - Bestari Ida Ayu Purnama; I Wayan Lasmawan; Desak Putu Parmiti3 (Jurnal Pendidikan Biologi Undiksha, 2025)
This study examines the perceptions, practices, and interests of young people toward Usadha Bali in the digital era, using a case study based on a survey in several regions of Bali and an in-depth case study in Buleleng Regency. Employing a qualitative approach with questionnaires (N=193) and in-depth interviews (N=30), the research reveals a significant paradox: the vast majority of young people (97.93%) are highly dependent on modern pharmaceuticals, yet 67.54% have experience using traditional medicine. Formal knowledge of Usadha Bali manuscripts is very low (85.86% have never heard of them), but 68.39% have medicinal plants at home and 80.85% are interested in learning about them. The high enthusiasm (92.63%) for the digitalization of Usadha Bali indicates that the knowledge gap is not due to resistance, but to limited access and inadequate dissemination methods. The main obstacles include lack of knowledge about preparation, difficulty accessing ingredients, and the perception that the process is complicated. The study concludes that Usadha Bali is experiencing conceptual knowledge erosion, yet has strong revitalization potential through digital platforms and contextual education.